Susceptibility of tumour necrosis factor-alpha genetically deficient mice to Trypanosoma congolense infection - Iraqi, F.A.; Sekikawa, K.; Rowlands, G.J.; Teale, A.J. (Wiley, 2001)
The TNF-alfa gene on mouse chromosome MMU17 is among the candidates for the trypanosomosis resistance QTG Tirl. Tit t has the largest effect of those loci so far detected which influence degree of resistance to murine trypanosomosis caused by Trypanosome congolense infection. We therefore studied the survival to 180 days after challenge with T. congolense of mice that were homozygous and hemizygous with respect to a disruption of the TNF-alfa gene on a > 99% C57BL/6 (resistant) background. We also examined the responses of TNF-alfa hemizygous mice produced by crossing the deletion line with mice of the C57BL16J strain, and with mice of the susceptible AlJ strain. Mice lacking a functional TNF-a gene were shown to be highly susceptible to challenge with T. congolense with a median survival time of 37 days. This was comparable- to. 71 days. far control wild-type mice, and 61 and 111 days for mice of the susceptible AlJ and resistant C57BL16J strains, respectively. In mice of the deletion line, the C57BU6 TNF-alfa allele tended to be dominant to the TNF knockout in terms of resistance. We conclude that TNF-alfa plays an important role in resistance to the effects of T. congolense infection in mice.